Author Correction: Sas-4 provides a scaffold for cytoplasmic complexes and tethers them in a centrosome - Jayachandran Gopalakrishnan (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.